UPAYA MENINGKATKAN AKTIVITAS BELAJAR SISWA DALAM MATA PELAJARAN IPA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) DI KELAS VIII.2 SMPN 3 PARIANGAN - Yuniazaida Yuniazaida (STKIP Pesisir Selatan, 2018)
ABSTRACTBased on the learning activities of Class VIII.2 students of SMPN 3 Pariangan in science subjects it was found that student learning activities in science subjects were still very low. The purpose of this study was to describe and obtain information about the Efforts to Improve Student Learning Activities in Science Subjects through the Numbered Heads Together (NHT) Cooperative Learning Model in Class VIII.2 of SMP 3 Pariangan. This research is a classroom action research. The research procedures in this study include planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 23 students of Class VIII.2 of SMP 3 Pariangan. The research data was collected using an observation sheet. Data were analyzed using percentages. Based on the results of the research and discussion that have been stated in the previous chapter, it can be concluded that it can be concluded that the Cooperative Learning Model Numbered Heads Together (NHT) can improve student learning activities in science subjects at Pariangan Middle School. Student Learning Activities from cycle I to cycle II. Student learning activities in the first cycle were 74.69 (sufficient) to increase to 82.53 (good) with an increase of 7.84